2016
DOI: 10.1186/s12916-016-0748-6
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of notifications to health practitioner boards: a retrospective cohort study

Abstract: BackgroundMedical boards and other practitioner boards aim to protect the public from unsafe practice. Previous research has examined disciplinary actions against doctors, but other professions (e.g., nurses and midwives, dentists, psychologists, pharmacists) remain understudied. We sought to describe the outcomes of notifications of concern regarding the health, performance, and conduct of health practitioners from ten professions in Australia and to identify factors associated with the imposition of restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…Dentists, including general dentists and dental specialists, are at higher risk of complaints to health regulators than any other registered health profession in Australia. Most of the complaints about dentists and dental prosthetists related to treatments and procedures, which may reflect the high risk, and often irreversible, nature of procedures such as prosthodontics, endodontics, restorative dentistry, oral surgery, implants and orthodontics . In addition, dentists work on conscious patients and do many procedures per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentists, including general dentists and dental specialists, are at higher risk of complaints to health regulators than any other registered health profession in Australia. Most of the complaints about dentists and dental prosthetists related to treatments and procedures, which may reflect the high risk, and often irreversible, nature of procedures such as prosthodontics, endodontics, restorative dentistry, oral surgery, implants and orthodontics . In addition, dentists work on conscious patients and do many procedures per day.…”
Section: Discussionmentioning
confidence: 99%
“…AHPRA provided us with data on all health practitioners registered between 1 January 2011 and 31 December 2016. This ‘practitioner extract’ consisted of variables indicating the period during which each practitioner was registered; the practitioner's age band, sex, profession and state or territory of practice, and the remoteness (as defined by the Australian Standard Geographical Classification Remoteness Structure) based on the main practice location provided by the practitioner …”
Section: Methodsmentioning
confidence: 99%
“…Further, any person may lodge a notification of sexual misconduct. Substantiated allegations can trigger sanctions ranging from a caution to cancellation of registration …”
Section: Methodsmentioning
confidence: 99%
“…Bismark et al 4,7,8 assessed complaint data gathered by the national regulator, the Australian Health Practitioner Regulation Agency (AHPRA), and identified trends and risk factors across and within the regulated health professions. In a retrospective study of all notifications made to AHPRA during 2011 and 2012 (excluding New South Wales (NSW)) concerning the original 10 regulated professions, Spittal et al 9 found that the notification rate was highest among doctors and dentists and lowest among nurses and midwives. Spittal et al 9 reported that the likelihood of 'restrictive action' (a broad category that included voluntary undertakings and conditions, as well as suspension or deregistration) was higher for cases involving impairment, improper prescribing or use of medication, and sexual misconduct than for cases involving clinical care.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In a retrospective study of all notifications made to AHPRA during 2011 and 2012 (excluding New South Wales (NSW)) concerning the original 10 regulated professions, Spittal et al 9 found that the notification rate was highest among doctors and dentists and lowest among nurses and midwives. Spittal et al 9 reported that the likelihood of 'restrictive action' (a broad category that included voluntary undertakings and conditions, as well as suspension or deregistration) was higher for cases involving impairment, improper prescribing or use of medication, and sexual misconduct than for cases involving clinical care. Doctors were less likely to face restrictive action than all the other professions.…”
Section: Previous Studiesmentioning
confidence: 99%